A revolution in fragments : traversing scales of justice, ideology, and practice in Bolivia - Goodale, Mark (Duke University Press, 2019)
"The years between 2006 and 2015, during which Evo Morales became Bolivia's first indigenous president, have been described as a time of democratic and cultural revolution, world renewal (Pachakuti), reconstituted neoliberalism, or simply, "the process of change." In A Revolution in Fragments Mark Goodale unpacks these various analytical and ideological frameworks to reveal the fragmentary and contested nature of Bolivia's radical experiments in pluralism, ethnic politics, and socioeconomic planning. Privileging the voices of social movement leaders, students, indigenous intellectuals, women's rights activists, and many others, Goodale uses contemporary Bolivia as an ideal case study with which to theorize the role that political agency, identity, and economic equality play within movements for justice and structural change"--